Literature Review: Terapi Komplementer untuk Mengurangi Nyeri Persalinan di Berbagai Negara - Malinda Capri Nurul Satya (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2023)
Labor pain is one of the most severe and can make it uncomfortable. If the problems of pain haven’t been resolved, it caused several symptoms such as anxiety, fear, and stress which can increase the intensity of the pain. This literature review aims to identify complementary therapies to reduce labor pain in various countries. The author searched articles in databases Google Scholar, Science Direct, Pubmed, and Cochrane. The criteria for articles in the form was quantitative research published in 2014-2019 with locations in various countries. The author reviews 6 articles on therapy complementary to reduce labor pain in various countries such as Turkey, Iran, Egypt, Brazil, and Indonesia. The author identified 7 complementary therapies used to reduce labor pain. This research used RCT (Randomized Controlled Trial) and quasi-experiment methods with VAS (Visual Analogue Scale) instruments. The methods such as breathing using lavender aromatherapy, music therapy, birth ball, heat therapy, cold therapy, acupressure, and hypnobirthing can be used. This therapeutic method is highly recommended to reduce pain and reduce anxiety during labor. In addition, this method has very few side effects and saves costs.